A deletion variant in LMX1B causing nail–patella syndrome in Japanese twins - Nozomu Kishio; Kazuhiro Iwama; Sayuri Nakanishi; Ryosuke Shindo; Masaki Yasui; Naoki Nicho; Atsushi Takahashi; Mana Kohara; Michisato Hirata; Takahiro Kemmotsu; Miki Tanoshima; Shuichi Ito (Human Genome Variation)
Abstract Nail–patella syndrome (NPS) is a hereditary disease caused by pathogenic variants in LMX1B and characterized by nail, limb, and renal symptoms. This study revealed a likely pathogenic LMX1B variant, NM_002316.4: c.723_726delinsC (p.Ser242del), in Japanese twins with clubfoot. The patients’ mother, who shared this variant, developed proteinuria after delivery. p.Ser242del is located in the homeodomain of the protein, in which variants that cause renal disease tend to cluster. Our findings highlight p.Ser242del as a likely pathogenic variant, expanding our knowledge of NPS.